Answer:
The function rule in slope-intercept form is:
![y = (1)/(2)x-(7)/(2)](https://img.qammunity.org/2021/formulas/mathematics/college/6p3p4uwj6vxwir5m4ri4uncszjp53nc39q.png)
Explanation:
The slope-intercept form of a function is given as:
![y = mx+b](https://img.qammunity.org/2021/formulas/mathematics/high-school/65dxh1fg3jfjanwatlvuvqa4t096a6as1k.png)
Here
m is the rate of change of function and b is the y-intercept
The rate of change is calculated as:
![m = (difference\ in\ y)/(difference\ in\ x)](https://img.qammunity.org/2021/formulas/mathematics/college/6pkd1652shtti9abxxejoisz3u01s8ti5u.png)
For this, any two pairs of input and output can be taken.
So using the pairs (1,-3) and (2,-1)
![m=(2-1)/(-1+3)\\=(1)/(2)](https://img.qammunity.org/2021/formulas/mathematics/college/x8jd37dhaqg4x6l2adc66lgrd83hnqcrsa.png)
Putting the value of slope in slope-intercept form
![y = (1)/(2)x+b](https://img.qammunity.org/2021/formulas/mathematics/college/62lueiq781q5j0e2dscvz6june8wvogn26.png)
Putting (1,-3) in the equation
![-3 = (1)/(2)(1)+b\\-3 = (1)/(2)+b\\b = -3-(1)/(2)\\b = (-6-1)/(2)\\b= (-7)/(2)](https://img.qammunity.org/2021/formulas/mathematics/college/2g97yesgo34ea30ow2yl8kqzbo6zau3qro.png)
Putting the value of b
![y = (1)/(2)x-(7)/(2)](https://img.qammunity.org/2021/formulas/mathematics/college/6p3p4uwj6vxwir5m4ri4uncszjp53nc39q.png)
Hence,
The function rule in slope-intercept form is:
![y = (1)/(2)x-(7)/(2)](https://img.qammunity.org/2021/formulas/mathematics/college/6p3p4uwj6vxwir5m4ri4uncszjp53nc39q.png)